Evaluation estuarine and coastal bathymetry changes of Cua Viet using Digital Elevation Model. - Nguyễn, Văn Cư (Trường Đại học Thủy Lợi, 2020)
Cua Viet is the Thach Han river’s mouth. It is quite big estuary that is located in the central coastal province of Quang Tri. In which, Cua Viet port plays an important role for water transport and commerce of the province. In recent years, accretion and erosion have occurred increasingly in term of scale and intensity. In addition, estuarine access channels suffer severely from sedimentation. Until now, there is no effective measure to train this estuary and Cua Viet morphological changes effect to navigation, flood control and other economic activities. In the frame work of this paper, bathymetry changes of Cua Viet estuary, especially access channels to Cua Viet port are deeply evaluated by setting up digital elevation model (DEM) based on in situ measured